2012
DOI: 10.1057/jt.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between brand personality and customer personality, gender and income: A case study of the cell phone market in Iran

Abstract: works as a Lecturer at the university of Tehran faculty of management, and faculty of entrepreneurship. He has been covering courses related to marketing, branding and marketing communication. Majid Hassani Nezhadis currently a PhD Candidate of Business Management in Allameh Tabatabai University. He has a Bachelor ' s degree in management and a Master ' s in marketing management from Shahid Beheshti University. His Master ' s thesis was a B2B perspective of relationship marketing in home appliances industry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Among compliant consumers; sophistication, competence and androgen dimensions of brand personality have significant positive effects on brand loyalty for Samsung brand. This is in accordance with the findings of Ekhlassi et al (2012) on Samsung, which showed the positive relations between personalities (extroversion, conscientiousness and agreeableness)…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among compliant consumers; sophistication, competence and androgen dimensions of brand personality have significant positive effects on brand loyalty for Samsung brand. This is in accordance with the findings of Ekhlassi et al (2012) on Samsung, which showed the positive relations between personalities (extroversion, conscientiousness and agreeableness)…”
Section: Discussionsupporting
confidence: 93%
“…Khani et al (2013) studied the customer personality and brand personality adoption and their effects on attitudinal and behavioral loyalty among Samsung mobile phone customers in Tehran. They have found that the adoption of the two traits improve brand equity and loyalty Ekhlassi et al (2012). also studied the cell phone market in Tehran and questioned the relationships between gender, customer personalities, income level and brand personality.…”
mentioning
confidence: 99%
“…The trait-based theories of personality try to describe human being in one or more series of traits (Das, 2014). Ekhlassi et al (2012) classify personality traits into five factors which are extroversion, agreeableness, conscientiousness, neuroticism, and openness. These factors above are normally referred to as the Big Five Model, which is commonly used to explain human behaviour.…”
Section: The Trait Theorymentioning
confidence: 99%
“…"Personality" can make a particular brand stand out in terms of the difference between the product and other products, along with stories about the product that could be conveyed to customers (Bhargava, 2008). The study of consumer psychology believes that consumers like to purchase something that is similar to themselves (Ekhlassi, Nezhad, Far, & Rahmani, 2012). According to Park (2011), consumers often prefer and would choose brands which could affirm their personality and enhance their sense of self.…”
mentioning
confidence: 99%
“…According to Park (2011), consumers often prefer and would choose brands which could affirm their personality and enhance their sense of self. Most of the studies measured brand personality with brand love, brand loyalty, brand image, the advertising and personality traits (Cohen, 2010;Ekhlassi et al, 2012;King, 2007;Park, 2011) and brand personality toward specific brand (Champniss & Vila, 2011;Ferrandi, Merunka, Valette-Florence, & Barnier, 2002;Mikkelsen;Thomas & Sekar, 2008;Till & Heckler, 2009). However, these studies did not focus on the direct effect and relationship of brand personality on consumers' buying decision.…”
mentioning
confidence: 99%